Exploration of biodiversity and evenness of bryophytes in mount of bogor, Indonesia - Ristanto, Rizhal Hendi; Sihab, Mutia Ayaar; Putri, Ririn Anindiana; Fitria, Rizky Nur; Darmawan, Ericka; Sigit, Diana Vivanti; Birran, Regan A.K.P.Y (JPBIO (Jurnal Pendidikan Biologi), 2025)
The geographical circumstances and rainfall in Bogor, Indonesia, contribute to the region's vast diversity of bryophyte.  There aren't many studies that show the diversity of Bryophyta in the mountains. The study focuses on the exploration of Bryophytes in Curug Cilember and Curug Ngumpet to compare their diversity and evenness levels. The method used is an exploration method with purposive sampling. The results have identified 21 Bryophyte species in Mount Hambalang and 9 species in Mount Bunder. The analysis of diversity index in Mount Bunder and Mount Hambalang generated a value of 2.838 and 1.992, respectively. These values are within the criteria of moderate diversity. The evenness index for both areas is 0.932 and 0.906, respectively, which indicates a high evenness. The differences in the research are due to differences in environmental factors, consisting of temperature, humidity, and light index in both locations.